Measurement of electrons from semileptonic heavy-flavor hadron decays in pp collisions at √s = 2.76 TeV - Abelev, Betty; Angelov, Venelin; Busch, Oliver; Glässel, Peter; Klein, Jochen; Leardini, Lucia; Lohner, Daniel; Lu, Xianguo; Maire, Antonin; Oyama, Ken; Pachmayer, Yvonne C.; Reygers, Klaus; et al. (Physical review. D, Particles, fields, gravitation, and cosmology, 2015)
The pT-differential production cross section of electrons from semileptonic decays of heavy-flavor hadrons has been measured at midrapidity in proton-proton collisions at √s=2.76  TeV in the transverse momentum range 0.5<pT<12  GeV/c with the ALICE detector at the LHC. The analysis was performed using minimum bias events and events triggered by the electromagnetic calorimeter. Predictions from perturbative QCD calculations agree with the data within the theoretical and experimental uncertainties.
*ALICE Collaboration: B. Abelev, V. Angelov, O. Busch, P. Glaessel, J. Klein, L. Leardini, D. Lohner, X.G. Lu, A. Maire, K. Oyama, Y. Pachmayer, K. Reygers, R. Schicker, J. Stachel, J. Stiller, M.A. Voelkl, B. Windelband, M. Winn, A. Zimmermann [und 923 weitere Personen]
Im Titel steht der Buchstabe s unter dem Wurzelsymbol
Gesehen am 14.07.2021